METHOD FOR DEPRESSING IRON SULPHIDES AND OTHER DISPOSABLE ELEMENTS DURING THE FLOTATION CONCENTRATION OF MINERALS, AND ELECTROCHEMICAL REACTOR - LAÍN RODRÍGUEZ, Eva María (2018)
A method and an electrochemical reactor are disclosed for depressing iron sulphides and other disposable elements during the flotation concentration of minerals. The proposed invention consists of a method based on the action of electrodes on the mineral, and can replace, complement or minimise the use of chemical reagents, and also improve their effect. Proceso para la depresión de sulfuros de hierro y otros elementos desechables en la con- centración de mineral por flotación y reactor electroquímico. La invención propuesta repre- senta un método basado en la acción de electrodos sobre el mineral, pudiendo sustituir, complementar o minimizar el consumo de reactivos químicos, así como mejorar su efecto. L'invention concerne un procédé pour la dépression de sulfures de fer et d'autres éléments jetables dans la concentration de minéral par flottation, ainsi qu'un réacteur électrochimique. Cette invention décrit un procédé basé sur l'action des électrodes sur le minéral, pouvant substituer, compléter ou minimiser la consommation de réactifs chimiques ainsi qu'améliorer leur effet.